Pengaruh Self Regulated Learning Dan Pola Asuh Orang Tua Terhadap Prokrastinasi Akademik Mahasiswa - Chotimah, Chusnul; Nurmufida, Lukluk (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Procrastination is a tendency to delay the completion of tasks by doing other activities that are not useful so that the task becomes obstructed, not completed on time, and often too late. These academic tasks include the task of writing papers, reading, studying exams, attending meetings (lectures), administrative duties, and overall academic performance. This study aims to determine the effect of self-regulated learning, parenting styles, and the enrollment years on the academic procrastination of the student of Faculty of Tarbiyah and Teaching Science IAIN Tulungagung.Â This was an ex-post facto study employing the quantitative approach. The research population comprised students of the Faculty of Tarbiyah and Teaching Science IAIN Tulungagung, in the enrolment years of 2017-2018 with a total of 3,728 students. The sample was using the proportionate stratified random sampling technique. The data were collected through questionnaires, and documentation, they were analyzed by means of the multiple regression technique.Â The results of the study at a significance level of 5% are as follows; There is a significant negative effect of the self-regulated learning on the academic procrastination indicated by a regression coefficient of -0.601 (p 0.05). There is a significant negative effect of the authoritative parenting style on the academic procrastination, indicated by a regression coefficient of -4.082 (p 0.05). The negative regression coefficient indicates that the academic procrastination due to the authoritative parenting style is lower than that due to the permissive parenting style. The study also shows that the student in the enrolment years of 2015 has a significant positive effect on the academic procrastination, indicated by a regression coefficient of 2.381 (p 0.05). Meanwhile, the student in the enrolment years of 2012 indicates a significant positive effect on the academic procrastination with a regression coefficient of 2.112 (p 0.05). And there is a significant effect of self-regulated learning, parenting styles, and enrolment years as an aggregate on the academic procrastination, indicated by a determination coefficient (R2) of 0.474 (p 0.05).